دور الفيسبوك في تعزيز الهوية الوطنية لدى الطلبة الجامعيين - ذيب, محمد; بن وهيبة, نورة (جامعة الوادي - University of Eloued, 2022)
تهدف الدراسة إلى تسليط الضوء على كيفية تعزيز الهوية الوطنية،عبر وسائل التواصل الإجتماعي-الفيسبوك– فنحن في عصر تدفق وانفجار المعلومات ، عصر الحضارة أو التنمية المعلوماتية أو عصر المعرفة والإنفتاح على الثقافات المختلفة والعولمة كما يطلق عليه ، والذي يسهم في تشكيل هوية ثقافية للفرد ،وبوجود هوية ثقافية وطنية جزائرية خاصة بالفرد الجزائري والطالب الجامعي كفرد واعي ومثقف ، وبوجود مثل هذه الوسيلة الإتصالية والتواصلية فيمكن أن نعتبر انه قد يكون لها دور في تعزيز هذه الهوية الوطنية الجزائرية لدى الطالب الجامعي ، خاصة منها تلك المضامين والمنشورات المتعلقة بمقوم الدين أو اللغة أو التاريخ الوطني أو اللباس أو غير ذلك مما له صلة بالهوية الجزائرية ، هذا من منطلق أن هذه الوسيلة تتسم بالشمولية والإتاحة بالموازات مع الطفرة التي شهدتها الجزائر في الآونة الأخير في مجال الإتصالات والتي تمثلت في إتاحة الجيل الثالث والرابع من الأنترنت والتي جعلت من النادر أن نجد طالباً جامعيًا لا يستخدم الفيسبوك . Abstract: The study aims to shed light on how to strengthen the national identity through the means of social communication - Facebook - we are in the era of information flow and explosion, the era of civilization or information development or the age of knowledge and openness to different cultures and globalization as it is called, which contributes to the formation of a cultural identity of the individual, And the existence of an Algerian national cultural identity of the Algerian individual and university student as a conscious individual and educated, and with such a means of communication and communication, we can consider that it may have a role in promoting this Algerian national identity of the university student, especially those contents and publications In relation to the denominator of religion, language, national history, dress, etc., which is related to Algerian identity, in view of the fact that this method is comprehensive and available in parallel with the recent boom in communications in Algeria, namely the availability of the third and fourth generations of the Internet, It has made it rare to find a college student who does not use Facebook.
مقال
Keywords: هوية وطنية؛ عولمة ثقافية؛ فيسبوك؛ طالب جامعي؛ جامعة; National Identity; Cultural globalization; Facebook University student; University